2013
DOI: 10.3389/fnsys.2013.00032
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of the thalamus for language capacities

Abstract: Early biological concepts of language were predominantly corticocentric, but over the last decades biolinguistic research, equipped with new technical possibilities, has drastically changed this view. To date, connectionist models, conceiving linguistic skills as corticobasal network activities, dominate our understanding of the neural basis of language. However, beyond the notion of an involvement of the thalamus and, in most cases also, the basal ganglia (BG) in linguistic operations, specific functions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 110 publications
(155 reference statements)
3
63
0
3
Order By: Relevance
“…Subcortical activation of the movie‐watching fMRI was in the right thalamus and basal ganglia (putamen and pallidum), while that of the task‐based fMRI was in the left thalamus and basal ganglia (putamen and caudate nucleus). The thalamus and basal ganglia have been hypothesized to play a role in the control and adaptation of corticocortical connectivity, and support for the composition of cortically provided information, respectively . The corticothalamic language processing network in the left hemisphere has recently been supported by structural connectivity analyses among Broca's area, basal ganglia, and thalamus using diffusion‐weighted imaging fiber tracking technique .…”
Section: Discussionmentioning
confidence: 99%
“…Subcortical activation of the movie‐watching fMRI was in the right thalamus and basal ganglia (putamen and pallidum), while that of the task‐based fMRI was in the left thalamus and basal ganglia (putamen and caudate nucleus). The thalamus and basal ganglia have been hypothesized to play a role in the control and adaptation of corticocortical connectivity, and support for the composition of cortically provided information, respectively . The corticothalamic language processing network in the left hemisphere has recently been supported by structural connectivity analyses among Broca's area, basal ganglia, and thalamus using diffusion‐weighted imaging fiber tracking technique .…”
Section: Discussionmentioning
confidence: 99%
“…Although, to the best of our knowledge, no human studies have addressed the connection between the thalamus and anterior temporal lobe, a recent tractography study demonstrated connections between the left frontal operculum (Broca's area) and the anterior ventral thalamus (Ford et al, 2013). Previous clinical and functional neuroimaging studies have suggested that various thalamic and cortical structures cooperate flexibly in a variety of language processing tasks (Klostermann, Krugel, & Ehlen, 2013;Llano, 2013). However, empirical evidence for the roles of individual thalamic nuclei in specific language functions, e.g., articulation, phonological processing and lexicosemantic processing, is scarce at present.…”
Section: Thalamo-cortical Network For Language/semantic Processingmentioning
confidence: 97%
“…It is known that thalamus and basal ganglia play an important role in word generation, and recent data suggest that the thalamus acts as a central monitor for language-specific cortical activities, supported by the basal ganglia in both perceptual and productive language execution. 47 Moreover, the insular cortex plays an important role in speech and emotional experience, and it has been demonstrated that hypometabolism of the anterior insula is associated with progressive nonfluent aphasia. 48 Furthermore, MRI studies have shown that the insula is interconnected with the temporal and orbitofrontal cortices and inferior frontal gyrus.…”
mentioning
confidence: 99%